2015
DOI: 10.4236/ns.2015.711052
|View full text |Cite
|
Sign up to set email alerts
|

The Approaching New Grand Solar Minimum and Little Ice Age Climate Conditions

Abstract: By about 2030-2040, the Sun will experience a new grand solar minimum. This is evident from multiple studies of quite different characteristics: the phasing of sunspot cycles, the cyclic observations of North Atlantic behaviour over the past millennium, the cyclic pattern of cosmogenic radionuclides in natural terrestrial archives, the motions of the Sun with respect to the centre of mass, the planetary spin-orbit coupling, the planetary conjunction history and the general planetary-solar-terrestrial interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 30 publications
(52 reference statements)
1
19
1
Order By: Relevance
“…This is obtained measuring the high of the present day sea level on the submerged quarry floor. This estimation of RSL is in good agreement with what was derived from proxy data on salt-marsh sediments and assemblages of foraminifera for the LIA [61]. Moreover, data of the submerged quarries of the Alghero area allow the conclusion that the rate of relative sea-level rise occurred during the last 200 years; that is, since 1809-1821 AD [60].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This is obtained measuring the high of the present day sea level on the submerged quarry floor. This estimation of RSL is in good agreement with what was derived from proxy data on salt-marsh sediments and assemblages of foraminifera for the LIA [61]. Moreover, data of the submerged quarries of the Alghero area allow the conclusion that the rate of relative sea-level rise occurred during the last 200 years; that is, since 1809-1821 AD [60].…”
Section: Discussionsupporting
confidence: 87%
“…This could be related 1) to quarry flooding, and 2) to the end of the exploited material. During this part of LIA (coincident with the Maunder minimum), sea level was at its minimum [61]. Thus, it seems unlikely to relate the moving to quarry floor flooding.…”
Section: Discussionmentioning
confidence: 93%
“…Herein we hypothesize that the 2100-2500 yr oscillation in the radiocarbon records has an astronomical origin, and search whether an astronomical record clearly manifests such an oscillation. In this regard, Charvátová (2000) was the first in suggesting that the observed 2100-2500 yr oscillation could be caused by the solar inertial motion, that is by the wobbling of the Sun around the barycenter of : Mörner, 2015;Scafetta, 2010Scafetta, , 2012a. Moreover, again using a simplified model, Scafetta (2012c) showed that the conjunctions of Jupiter and Saturn, using their tropical orbital periods, fully precess over a quasi 2400 year period.…”
Section: Introductionmentioning
confidence: 97%
“…A planetary origin of solar and climate oscillations, which has been proposed since antiquity, does have numerous empirical evidences and some preliminary explanations (e.g. : Abreu et al, 2012;Charvátová, 2009;Cionco and Soon, 2014;Hung, 2007;Fairbridge, 1984;Fairbridge and Sanders, 1987;Jakubcová and Pick, 1986;Jose, 1965;McCracken et al, 2013McCracken et al, , 2014Mörner, 2013Mörner, , 2015Mortari, 2010;Puetz et al, 2014;Salvador, 2013;Scafetta, 2010Scafetta, , 2012aScafetta, ,b, 2013Scafetta, , 2014aScafetta, , 2016Scafetta and Willson, 2013a,b;Sharp, 2013;Solheim, 2013;Tan and Cheng, 2013;Tattersall, 2013a,b;Wilson, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the best prediction for a sea level change at year 2100 seems to be +5 cm ± 15 cm [30], in strong disagreement to numerous models (all lacking validation in observational facts) as illustrated in Figure 4 from [31]. (from [34] [35]). This implies that we, in two decades will be in the low of a New Grand Solar Minimum and in climate conditions like previous Little Ice Ages.…”
Section: Sea Level Changesmentioning
confidence: 94%